2022
DOI: 10.1039/d1sm01241j
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional compaction of soft granular packings

Abstract: This paper analyzes the compaction behavior of assemblies composed of soft (elastic) spherical particles beyond the jammed state, using three-dimensional non-smooth contact dynamic simulations. The assemblies of particles are characterized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 70 publications
6
30
0
Order By: Relevance
“…2 go as high as 0.9. Recent studies 56 have shown that classical DEM is not accurate at such high compression, due to extreme deformations, so that particles are not spherical anymore, with additional, multiple contacts established. Different methods, e.g.…”
Section: Classical Analysis Of Dem Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 go as high as 0.9. Recent studies 56 have shown that classical DEM is not accurate at such high compression, due to extreme deformations, so that particles are not spherical anymore, with additional, multiple contacts established. Different methods, e.g.…”
Section: Classical Analysis Of Dem Resultsmentioning
confidence: 99%
“…Before closing this introduction, we point out that in the present work we also consider relative large volume fractions, that may lead to large particle deformations, which in turn could produce new contacts between particles. Recently, there have been a few studies to tackle the realistic behavior of highly deformable particles both numerically 51–56 and experimentally. 27,57–59 In the present paper the soft-DEM numerical approach is used to model the compaction of “soft” elastic grains; in this approach the change of shape of the grains is neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Although many equations have been proposed in the last decades to try to link the confining pressure to the compactness [50,51,52,53], most of them are based on empirical strategies with no apparent physical bases, requiring several fitting parameters. Only recently, a systematic approach, based entirely on micromechanical parameters and free of any ad hoc parameters, has been proposed and numerically tested in the case of hyperelastic circular, polygonal, and spherical shapes under different frictionnal conditions [45,46]. This method was derived from the micromechanical expression of the granular stress tensor together with the approximation of the Hertz contact law between two particles at small strain and the theoretical solution of the hydro-static compaction of a single particle.…”
Section: Compressing Squishy Particle Assembliesmentioning
confidence: 99%
“…In the case (ii), the unilaterality of contacts (non-regularized laws) traduces the non-penetration of the particles. Both [20]), (b) using the meshless approach MPM (with permission of S. Nezamabadi et al [41]), (c) using the meshless "soft-DEM" approach (with permission of G. Mollon [64]), (d) using the 3D Non-Smooth Contact Dynamics approach by M. Cardenas-Barrantes et al [46]. (e) Example of a T1-event running from time t 1 to t 3 .…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation